Guidance note on state owned enterprise reform in sovereign projects and programs. - Park, Cyn-Young
Under Strategy 2030, ADB is committed to SOE reform in its developing member countries (DMCs).The publication reviews the significance of SOEs in Asia and the Pacific, the role of SOE reform in ADB strategy, and related requirements for sovereign projects. SOE challenges are also assessed with a focus on projects, policy based loans (PBLs), and sector programs.Although the publication is designed to guide ADB staff in their work with SOEs through sovereign projects, PBLs, and technical assistance, it may also be of use to DMC officials and SOE boards and management.